2013
DOI: 10.1104/pp.113.216564
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Delivery of Zinc to Developing Tissues in Rice Is Mediated by P-Type Heavy Metal ATPase OsHMA2    

Abstract: Developing tissues such as meristems and reproductive organs require high zinc, but the molecular mechanisms of how zinc taken up by the roots is preferentially delivered to these tissues with low transpiration are unknown. Here, we report that rice (Oryza sativa) heavy metal ATPase2 (OsHMA2), a member of P-type ATPases, is involved in preferential delivery of zinc to the developing tissues in rice. OsHMA2 was mainly expressed in the mature zone of the roots at the vegetative stage, but higher expression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
262
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 360 publications
(291 citation statements)
references
References 33 publications
9
262
0
Order By: Relevance
“…Costaining with 49,6-diamidino-2-phenylindole (DAPI) showed that the fluorescence signal of OsHMA5 was located at peripheral region of the cells outside the nuclei. This localization was similar to OsHMA2, a plasma membrane-localized transporter of Zn and Cd (Yamaji et al, 2013), suggesting that OsHMA5 was also localized to the plasma membrane (Fig. 3, D-F).…”
Section: Cellular and Subcellular Localization Of Oshma5supporting
confidence: 53%
See 4 more Smart Citations
“…Costaining with 49,6-diamidino-2-phenylindole (DAPI) showed that the fluorescence signal of OsHMA5 was located at peripheral region of the cells outside the nuclei. This localization was similar to OsHMA2, a plasma membrane-localized transporter of Zn and Cd (Yamaji et al, 2013), suggesting that OsHMA5 was also localized to the plasma membrane (Fig. 3, D-F).…”
Section: Cellular and Subcellular Localization Of Oshma5supporting
confidence: 53%
“…A number of transporters for xylem loading have been identified. For example, AtHMA2 and AtHMA4 in A. thaliana and OsHMA2 in rice are responsible for xylem loading of Zn as well as Cd (Hussain et al, 2004;Verret et al, 2004;Yamaji et al, 2013). PHO1 in A. thaliana is involved in the transfer of inorganic phosphate from roots to shoots (Poirier et al, 1991;Chiou and Lin, 2011).…”
Section: Transport Activity Of Oshma5 In Yeastmentioning
confidence: 99%
See 3 more Smart Citations